1999
DOI: 10.1111/1467-9450.00114
|View full text |Cite
|
Sign up to set email alerts
|

Reactions following the sudden death of a classmate

Abstract: Findings from a study of adolescents grief reactions following the sudden accidental death of a friend and classmate are presented. The group (26 classmates) was followed up after one and nine months. Interviews and a questionnaire including the Impact of Event Scale and the Hogan Grief Inventory were used. The general grief scores on the Hogan Grief Inventory indicated that the grief level was similar to that of adolescents who had lost siblings. The scores on the Impact of Event Scale showed a decline in dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Most adolescent grief and loss studies have been gathered via surveys to assess the prevalence of bereavement experience within the adolescent population and tend to be descriptive in nature (cf. Balk, 1983;Dyregrov et al, 1999;McNeil, Silliman, & Swihart, 1991;Melhem et al, 2004;Noppe & Noppe, 1997;O'Brien et al, 1991;Rask, Kaunonen, & Paunonen-Ilmonen, 2002;Ringler & Hayden, 2000;Riordan & Beggs, 1987;ServatySeib & Pistole, 2007).…”
Section: Adolescent Grief and Loss Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most adolescent grief and loss studies have been gathered via surveys to assess the prevalence of bereavement experience within the adolescent population and tend to be descriptive in nature (cf. Balk, 1983;Dyregrov et al, 1999;McNeil, Silliman, & Swihart, 1991;Melhem et al, 2004;Noppe & Noppe, 1997;O'Brien et al, 1991;Rask, Kaunonen, & Paunonen-Ilmonen, 2002;Ringler & Hayden, 2000;Riordan & Beggs, 1987;ServatySeib & Pistole, 2007).…”
Section: Adolescent Grief and Loss Reactionsmentioning
confidence: 99%
“…Girls have been shown to grieve longer and react more strongly around loss than boys (Dyregrov et al, 1999). Girls are very attentive to and expressive regarding their emotions, as well as the reactions and feelings of those around them.…”
Section: What Bereaved Adolescent Girls Needmentioning
confidence: 99%
See 1 more Smart Citation
“…There is mounting evidence that girls report more reactions following death and trauma than boys do (Balmer, 1992, reported in Fleming & Balmer, 1996; Bolton et al , 2000; Burke, Moccia, Borus & Burns, 1986; Curle & Williams, 1996; Dyregrov, Matthiesen, Kristoffersen & Mitchell, 1994; Dyregrov, Gjestad, Bie Wikander & Vigerust, 1999; Giaconia et al , 1995; Green et al , 1991; Khoury et al , 1997; Vernberg, La Greca, Silverman & Prinstein, 1996). Higher rates of PTSD in women than men has been found to be a function of higher probability of PTSD development in women, not the prevalence or type of exposure (Breslau, Davis, Andreski, Peterson & Schultz, 1997), a finding supported in a study of older adolescents (Giaconia et al , 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty years after the loss widows thought about their partner at least every other week, and had a conversation with the partner once a month. Dyregrov, Gjestad, Bie Wikander, and Vigerust (1999) found that the majority of adolescents in their sample experienced grief 9 months after the sudden death of a classmate. A large percentage of the participants expected that they might never recover from the grief, or that it would take several years.…”
Section: Experiencing Griefmentioning
confidence: 97%